Hubungan Kebiasaan Bermain Video Game dengan Perkembangan Sosial Anak Sekolah Dasar (SD) - Suliswati Suliswati; Indriana Rakhmawati (Poltekkes Kemenkes Jakarta III, 2018)
The negative impact of playing video games can cause addiction, which affects the lack of socialization of children with peers. This study aims to determine the relationship between the habit of playing video games and the social development of elementary school children. The research design was crossectional. The research sample was 92 elementary school students in grades 4, 5 and 6. Sampling was done randomly. The results showed a significant relationship between the habit of playing video games with social development which included: length of play time 1.5 hours (p = 0.048), more than 2 hours (p = 0.048), playing game every day (p = 0.017), playing game every weekend (p = 0.013), and age of respondents (p = 0.019). Playing video games for 1.5 -> 2 hours has a very dominant relationship with the social development of elementary school children with an OR of 6.995. This showed that elementary school children who play video games for 1.5 -> 2 hours have a tendency to lack social achievement of 6 to 7 times. The conclusion is the length of the habit of playing video games which includes; the duration of playing video game of 1.5 -> 2 hours, the frequency of playing every week and every weekend, the age of elementary school children at elementry school has an impact on the lack of social development of children. Monitoring of parents on the habits of children playing video games must be done.